Correlation Between Corporate Entrepreneurship and Organizational Performance in Deposit Money Banks in Nigeria - Handsome-Idada, Shalom Peace; Ugwuanyi, Wilfred; Okoh, Johnson I. (NIU Journal of Social Sciences, 2024)
The study assessed the correlation between corporate entrepreneurship dimensions and performance of selected deposit money banks in Nigeria. Specific objectives include to: evaluate the correlation between corporate entrepreneurship dimensions (value creation) and customers’ retention and investigate the correlation between corporate entrepreneurship dimensions (competitive aggressiveness) and market value performance. A survey research design was used. Total population of the study was nine fifty (950) staff of Deposit Money Banks. Sample size was two hundred and eighty-one (281) using Taro Yamane formular. The convenient sampling method was adopted used while structured questionnaire was used as instrument for data collection. It was found that value creation had insignificant relationship with customers’ retention and competitive aggressiveness had a significant relationship with market value performance. Based on the findings, the study concluded that corporate entrepreneurship dimensions correlated significantly with performance of selected deposit money banks in Nigeria. The study recommends that it is highly recommended that value creation of top management should indulge the opinion of their customers through questionnaires and feedback mechanism. This would give the organisation an insight to what the customers’ expectations regarding new things that are brawling up in similar competitive organisations. In the same vein indulging customer’s opinion while launching new products, would make them feel carried along and valuable. Keywords: Corporate Entrepreneurship Organizational Performance, Deposit Money Banks